Kebiasaan merokok dan konsumsi garam berlebihan terhadap kejadian hipertensi pada lansia - Ilham Kamaruddin; Neti Sulami; Muntasir Muntasir; Zulkifli Zulkifli; Mauritz Pandapotan Marpaung (Holistik Jurnal Kesehatan, 2023)
Background: Hypertension is one of the non-communicable diseases that many people of productive age and the elderly suffer from today. The increase in the prevalence of hypertension is influenced by lifestyle, one of which is smoking and excessive salt consumption.Purpose: To determine the smoking habits and excessive salt consumption on hypertension occurrence among the elderly.Method: A cross-sectional research design with a population was the elderly who lived in the working area of the Mangger Health Centre. The number of samples in this study was 91 elderly. The sampling technique used is purposive sampling. The instrument used is a questionnaire. Data analysis using chi-square test.Results: Finding that there was an influence between smoking behavior on the incidence of hypertension in the elderly (0.040<0.05) and OR = 2.663. there is an influence between excessive salt consumption on the incidence of hypertension in the elderly (0.001<0.05) and OR= 4.948Conclusion: The elderly who smoke are 2.6 times more likely to suffer from hypertension compared to the elderly who do not smoke and the elderly who consume excess salt is 5 times more likely to suffer from hypertension compared to the elderly who do not consume excess saltSuggestion: Health workers to provide education to the public about efforts to prevent hypertension by improving lifestyle.Keywords: Smoking habits; Excessive salt consumption; Hypertension; Elderly.Pendahuluan: Hipertensi  merupakan  salah  satu  penyakit  tidak  menular  yang  banyak  diderita  oleh masyarakat usia produktif dan lansia saat ini. Peningkatan prevalensi hipertensi dipengaruhi oleh gaya hidup salah satunya adalah merokok dan konsumsi garam berlebih.Tujuan: Mengetahui pengaruh kebiasaan merokok dan konsumsi garam berlebihan terhadap kejadian hipertensi pada lansiaMetode: Penelitian cross sectional dengan populasinya lansia yang tinggal di wilayah kerja Puskesmas Mangger dan jumlah sampelnya sebanyak 91 lansia. Teknik sampel yang digunakan adalah purposive sampling. Instrumen yang digunakan adalah kuesioner. Analisis data menggunakan uji chi square.Hasil: Didapatkan adanya pengaruh antara perilaku merokok terhadap kejadian hipertensi pada lansia (0,040<0,05) dan OR=2,663. Ada pengaruh antara konsumsi garam berlebihan terhadap kejadian hipertensi pada lansia (0,001<0,05) dan OR= 4,948.Simpulan: Lansia yang merokok berpeluang 2,6 kali menderita hipertensi dibandingkan dengan lansia yang tidak merokok dan lansia yang mengkonsumsi garam berlebih berpeluang 5 kali menderita hipertensi dibandingkan dengan lansia yang tidak konsumsi garam berlebih.Saran: Disarankan kepada tenaga kesehatan untuk memberikan edukasi kepada masyarakat tentang upaya pencegahan hipertensi dengan memperbaiki gaya hidup.